Meta-Analisis Literasi Sains Siswa di Indonesia - Novita, Mery; Rusilowati, Ani; Susilo, Susilo; Marwoto, Putut (UPEJ Unnes Physics Education Journal, 2021)
Scientific literacy skills are very important in the era of globalization, where science and technology are rapidly developing, especially in developed countries. Science and technology in particular have a very big role in improving the quality of a country's education. The low scientific literacy of students in Indonesia makes Indonesia rank 70 out of 79 countries participating in international scientific literacy assessments. Students 'scientific literacy skills must receive special attention, namely by looking for causes and efforts to improve students' scientific literacy, especially in Indonesia. The research objective is to determine the causes of low scientific literacy and how to improve it to assess the integrity of students' scientific literacy by mapping the research results from previous research at the science education level for both junior high and high school students. The type of research method used is the SLR (Systematic Literature Review) method. This research method is carried out by reviewing and identifying journals systematically with data results in the form of qualitative descriptive analysis.